A randomized algorithm for online metric b-matching - Kalyanasundaram, Bala; Pruhs, Kirk; Stein, Cliff (Operations research letters, 2023)
We give a randomized algorithm for online metric b-matching that is O(log2⁡k) competitive, where k is the number of server locations, by giving a black box reduction from b-matching on a hierarchically separated tree to a uniform metric space.